Design of Production Scheduling Applications on CV Aneka Karya Makmur - Kusumawati, Tiara Indah; Sudarmaningtyas, Pantjawati; Setyawan, Henry Bambang (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
CV Aneka Karya Makmur is a company engaged in the computer embroidery services are located in the hamlet Wonokoyo Kulon No 35, Beji Pasuruan. Today the company makes the production schedule just by looking at the list of orders are coming in which orders are coming in advance will be done. As a result, the waiting time high orders and orders that have little processing time required to wait too long. Solution to the problems above are improved methods of production scheduling. Scheduling applications make the selection of the best methods of four methods First Come First Serve (FCFS), Shortest Processing Time (SPT), Longest Process Time (LPT), and the Earliest Due Date (EDD), in which all four of these methods will be evaluated to obtain the best method , The parameters used to evaluate four methods is the average completion time, utilization, the average number of jobs in the system, and the average delay in the work. Based on the applications made and the testing that has been done, the value of the test reached 100%. This application can take orders, which can be directly carried out the manufacture of the production schedule by one of the best methods. This application can also produce evidence of orders and generate reports on the results of production scheduling.  Keywords: Production Scheduling, Ordering method, Priority Rules.